(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The advent of the 4th Industrial Revolution has made it inevitable for firms worldwide to modify their business models to integrate ICTs into their operations. The lockdown measures to contain the COVID-19 pandemic appear to have accelerated this process as many businesses, particularly in the hospitality industry, had to shut down their operations. Others also had to resort to conducting their businesses solely online. Thus, it has been argued that e-commerce has thrived during the lockdown period. Concentrating on the current 27 European Union (EU) member countries, this paper seeks to answer the following question: To what extent the COVID-19 impacted e-commerce has? Trend analyses and a paired samples t-test are used to compare the mean percentage of enterprises with e-commerce sales before the pandemic and the first year. The study finds a significant increase in the percentage of enterprises that made e-commerce sales during the first year of the pandemic compared to the previous year (t=-2.06; df=25). Except for the western EU member countries, all other regions increased the percentage of enterprises that made e-commerce sales, with the southern EU countries witnessing the highest increase.